2019
DOI: 10.1080/0267257x.2019.1632373
|View full text |Cite
|
Sign up to set email alerts
|

Celebrity influences on consumer decision making: new insights and research directions

Abstract: Throughout human history, people expressed admiration for heroes who possessed extraordinary abilities and achieved superhuman goals. For many, modern-day celebrities fulfil this role and are prominent in various marketing communications activities. This paper addresses the literature review gaps and provides an in-depth review of the psychological and social psychological perspectives which are relevant to the celebrity endorsement literature. The contributions of this paper consist of a detailed analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 163 publications
3
38
1
2
Order By: Relevance
“…Both groups of high and low EI showed interest in the advertising messages that depicted issues of famous and celebrity figures. This probably is due to the strong media presence and high level of popularity and strong influence of celebrities used to promote all kinds of products and causes in all aspects of life in most western societies [63,64].…”
Section: Resultsmentioning
confidence: 99%
“…Both groups of high and low EI showed interest in the advertising messages that depicted issues of famous and celebrity figures. This probably is due to the strong media presence and high level of popularity and strong influence of celebrities used to promote all kinds of products and causes in all aspects of life in most western societies [63,64].…”
Section: Resultsmentioning
confidence: 99%
“…Further, it has been observed that a credible celebrity can also help in inducing the desired behaviour with regards to the advertisement, brand and purchase intention [49,[54][55][56]. Lafferty and Goldsmith [48], Goldsmith et al [49] and Lafferty et al [44] demonstrated the significant effects of celebrity credibility on attitude towards advertisement, attitude towards brand and purchase intention.…”
Section: Celebrity Credibility and Celebrity Endorsementmentioning
confidence: 99%
“…Further, it has been observed that a credible celebrity can also help in inducing the desired behaviour with regards to the advertisement, brand and purchase intention [49,[54][55][56]. Lafferty and…”
Section: Celebrity Credibility and Celebrity Endorsementmentioning
confidence: 99%
See 1 more Smart Citation
“…However, considering that BCV is a new marketing communication tool and is still being explored, it would be interesting to observe if featuring a celebrity in a BCV would have any effect on consumer’s AB. This is important as most BCVs are consumed by Gen Z, a consumer cohort, which understands the nuances of CEs and are closer to celebrities than their older consumer cohorts (Moraes et al, 2019). The above discussion makes it essential to observe if the presence of a celebrity moderates the relationship between BCV and brand attitude, leading to the formation of the following hypotheses: H 6a : CE moderates the relationship between ENT and the dependent variable—AB. H 6b : CE moderates the relationship between INF and AB. H 6c : CE moderates the relationship between CR and AB. …”
Section: Literature Reviewmentioning
confidence: 99%